Efecto agudo de la ingestión de cafeína sobre el tiempo de reacción y la actividad electromiográfica de la patada circular Dollyo Chagi en taekwondistas - Cortez, L.; Mackay, K.; Contreras, E.; Penailillo, L. (Revista Internacional de Ciencias del Deporte, 2017)
Caffeine is considered an enhancing aid and most consumed in sports, mainly due to its stimulant properties on the central nervous system, improving athletic performance and decreasing muscle fatigue. Objective: The aim of this study was to investigate the acute effect of caffeine on the reaction time and muscle activity of a Dollyo Chagi kick in taekwondo fighters. Methods: Thirteen taekwondo fighters ingested either 5 mg of caffeine per kg of body mass or a placebo. Reaction time and muscle activity were measured 60 min before the intake of caffeine or placebo, 60 min after ingestion and after a fatigue stimuli. Surface electromyogram (sEMG) amplitude, and time of reaction of the muscles rectus femoris, vastus lateralis, vastus medialis and biceps femoris during a circular kick related to a sound stimulus were measured. Results: Caffeine ingestion decreased the reaction time of the rectus femoris muscle 60-minutes after ingestion of caffeine and after strenuous stimulation (P<0.05). No significant decrease in reaction time was observed in other muscles. Furthermore, no changes in muscles activity in any other muscles were found. Conclusion: Caffeine supplementation in taekwondo athletes could reduce the reaction time of a Dollyo Chagi round kick after 60 minutes of ingestion and after a fatigue stimuli.